A Study about Finding Exact Solutions for Zeldovich Equation with Time-Dependent Coefficients by Using the Tanh Function Method (Latakia University Journal -Basic Sciences Series, 2018)
In this work, we have been found explicit exact soliton wave solutions for Zeldovich equation with time-dependent coefficients, by using the tanh function method with nonlinear wave transform, in general case. The results obtained shows that these exact solutions are affected the nonlinear nature of the wave variable, it is also shown that this method is effective and appropriate for solving this kind of nonlinear PDEs, which are models of many applied problems in physics, chemistry and population evolution.